2018
DOI: 10.1038/modpathol.2017.185
|View full text |Cite
|
Sign up to set email alerts
|

Genome profiling is an efficient tool to avoid the STUMP classification of uterine smooth muscle lesions: a comprehensive array-genomic hybridization analysis of 77 tumors

Abstract: The diagnosis of a uterine smooth muscle lesion is, in the majority of cases, straightforward. However, in a small number of cases, the morphological criteria used in such lesions cannot differentiate with certainty a benign from a malignant lesion and a diagnosis of smooth muscle tumor with uncertain malignant potential (STUMP) is made. Uterine leiomyosarcomas are often easy to diagnose but it is difficult or even impossible to identify a prognostic factor at the moment of the diagnosis with the exception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 38 publications
1
29
2
2
Order By: Relevance
“…Therefore, especially in the setting of leiomyoma variants, results of genomic analysis should be interpreted carefully in correlation with the pathologic findings. That said, the majority of the tumors in our series showed simple genomic profiles (genomic index ranging from 0 to 19.3; mean 5.9), significantly different from the previously reported genomic profiles of leiomyosarcomas (with genomic index up to 180, and mean 51.8) 32 . Future studies - using other techniques (mutation and gene expression analyses) – may uncover additional genomic alterations not detectable by aCGH (mutations or balanced rearrangements) that may be responsible for the intravascular tumor location and the resulting aggressive clinical behavior in some patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, especially in the setting of leiomyoma variants, results of genomic analysis should be interpreted carefully in correlation with the pathologic findings. That said, the majority of the tumors in our series showed simple genomic profiles (genomic index ranging from 0 to 19.3; mean 5.9), significantly different from the previously reported genomic profiles of leiomyosarcomas (with genomic index up to 180, and mean 51.8) 32 . Future studies - using other techniques (mutation and gene expression analyses) – may uncover additional genomic alterations not detectable by aCGH (mutations or balanced rearrangements) that may be responsible for the intravascular tumor location and the resulting aggressive clinical behavior in some patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, a recent series by Croce et al . of 77 uterine smooth muscle tumors with a mean follow up of 63.6 months identified a genomic index cut off score of 10 as a predictor of recurrence and a criterion for “molecular leiomyosarcoma” 32 . Among stage 1 “molecular leiomyosarcomas” in that study, poor prognostic markers included genomic index cut-off score of 35, 5p gain, 13q loss involving RB1 and 17p gain involving MYOCD , the latter promoting smooth muscle differentiation and cell migration 73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D, Underexpressed genes in the low-proliferation group. studies using array CGH in uterine smooth-muscle tumors have indicated that genomic complexity is prognostic in that group of tumors (29,30). Our findings, in contrast, appear to indicate that genetic complexity is not prognostic in UUS, and thus chromosomal complexity as a prognostic marker is subtype specific.…”
Section: Discussioncontrasting
confidence: 60%
“…Eine MED12-Amplifikation findet sich sowohl in Leiomyomen als auch Leiomyosarkomen. Mittels der Array-CGH ("array-based comparative genomic hybridization") konnte eine Unterscheidung benigner von malignen glattmuskulären Tumoren getroffen und damit die STUMP-Kategorie vermieden werden [8]. Es scheint, dass mittels Genexpressionsprofilen Leiomyosarkome von Stromasarkomen des Endometriums unterschieden werden können [9].…”
Section: Diagnostische Probleme Von Glattmuskulären Uterustumorenunclassified